2019
DOI: 10.3389/fgene.2018.00690
|View full text |Cite
|
Sign up to set email alerts
|

Target of Rapamycin (TOR) Regulates the Expression of lncRNAs in Response to Abiotic Stresses in Cotton

Abstract: TOR (Target of Rapamycin) kinase is an evolutionarily conserved protein kinase, which integrates stress-related cues with growth and metabolic outputs. Long non-coding RNAs (lncRNAs) play a vital role in the regulation of eukaryotic genes. However, little is known about TOR's function in regulating the expression of lncRNAs in plants. In this study, four putative homologous genes encoding the TOR protein were identified by utilizing the recently completed cotton genome. Pharmacological experiments with TOR inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 115 publications
(184 reference statements)
0
16
0
Order By: Relevance
“…Rapamycin acts as an allosteric inhibitor of mTOR upon association with the FK506-binding protein 12 (FKBP12) (Yang et al, 2013); however, many plants are insensitive to it (Xiong and Sheen, 2015). Another TOR inhibitor, AZD8055, an efficient autophagy inducer that works by suppressing TOR signaling, is widely used in plants (Dong et al, 2015;Pu et al, 2017;Song et al, 2019). Several inhibitors of autophagy in plant cells have been reported to impact on different stages of the process.…”
Section: Chemical Inducers and Inhibitors Of Autophagymentioning
confidence: 99%
“…Rapamycin acts as an allosteric inhibitor of mTOR upon association with the FK506-binding protein 12 (FKBP12) (Yang et al, 2013); however, many plants are insensitive to it (Xiong and Sheen, 2015). Another TOR inhibitor, AZD8055, an efficient autophagy inducer that works by suppressing TOR signaling, is widely used in plants (Dong et al, 2015;Pu et al, 2017;Song et al, 2019). Several inhibitors of autophagy in plant cells have been reported to impact on different stages of the process.…”
Section: Chemical Inducers and Inhibitors Of Autophagymentioning
confidence: 99%
“…In cotton, previous studies have shown that lncRNAs XLOC_063105-CotAD_37096 and XLOC_115463-CotAD_12502 probably function in cis-regulating responses to drought stress [32]. One lncRNA, TCONS_00061835-Gh_D06G1439 (GhMYB-like), regulates cotton fiber development [36] by complementary base pairing with the protein-coding gene, lncRNA, and the circRNA complex network, demonstrating that some lncRNAs are involved in biotic and abiotic stresses [31,33,34].…”
Section: Lncrna In the Anther Development Of Cotton And Predicted Funmentioning
confidence: 99%
“…With the development of modern technology, the de novo assembly of Gossypium hirsutum and Gossypium barbadense genomes in high quality has improved contiguity and completeness in the available genome information [29,30]. In cotton, lncRNAs participate in resistance to Verticillium dahliae [31], drought stress [32], salt stress [33], and other abiotic stresses [34]. LncRNAs also participate in regulating fiber development [5,35] and in lint initiation [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since H3K27me 3 occupies the intergenic regions, we speculate that TOR impacts transcriptome through intergenic non-coding RNAs. In plants, AZD8055-mediated TOR inhibition can induce long non-coding RNA expression which is often marked by H3K27me 3 (Song et al, 2018). This suggests that global decrease of H3K27me 3 level in conditions of TOR inactivation could also affect transcription or translation through long non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%